Controle de velocidade sensorless de motores de indução trifásicos sujeitos a distúrbios de torque - Gastaldini, Cristiane Cauduro (2008)
This work presents a study of a sensorless speed servomechanism using threephase induction motors. The aim is to investigate the performance of a specific control technique when different load variations or torque disturbances are applied. In order to determine the control technique to be used, first a review of the state-of-the-art of control and speed estimation techniques with their characteristics and limitations. The proposed sensorless induction motor servomechanism uses indirect fieldoriented control (IFOC), a technique based on feedback linearization control (FLC), which is often used in nonlinear systems. This control system comprises three basic controllers: flux control, speed control and current control. To implement IFOC, estimates of torque and speed are required. Speed is estimated using an adaptive reference algorithm of reactive power. The resulting estimated is processed in a Kalman filter, which is also used for torque estimates. A number of simulations using the Matlab® software package and experimental results using on DSP TMS320F2812 platform are presented here to verify the performance of the proposed control system in conditions of low speeds and load variations.